Physical Activity in Relation to Wellbeing Among Newly Arrived Refugees in Sweden: A Quantitative Study - Katarina Sjögren Forss; Elisabeth Mangrio; Elisabeth Mangrio; Matti Leijon; Mathias Grahn; Slobodan Zdravkovic; Slobodan Zdravkovic (Frontiers Media S.A., 2021)
Background: Little is known about physical activity among newly arrived refugees and what impact physical activity might have on their health, as measured by mental wellbeing, vitality, stress and sleep quality. Thus, this study sought to investigate the relationship between physical activity and wellbeing among refugees who were newly arrived in Sweden.Methods: The present study was based on the results from a survey, conducted in 2015-2016 among newly arrived adult refugees who spoke Arabic, Pashto, Somali or Dari, participated in a mandatory public integration support programme in the Scania region of Sweden and agreed to participate in the survey. Ultimately 681 participants completed the survey (a response rate of 39.5%).Results: We found a significant association between physical activity and mental wellbeing, vitality, stress and sleep quality among newly arrived refugees.Conclusions: Newly arrived refugees need to be informed about the importance of prioritizing physical activity for their health and wellbeing, regardless of their external circumstances, and supported in their attempts to do so.